Mental health at work: stressors and coping mechanisms - Santa, Inês Marques dos Santos Fonte (2023)
The Covid-19 pandemic had dramatic consequences for workers’ mental health. Following the Demand-Resource Model, and using 2021 Eurofound’s survey, this paper evaluates whether, in Portugal, managers can offset the negative relation between job demands and workers’ health by giving them resources. Findings show that having colleagues support, ability to influence decisions, and fair payment decrease the likelihood of burnout (-18p.p.), anxiety (-18p.p.), and depression (-7p.p.), respectively. Managers’ priority should be to reduce pressure coming from work-life unbalance, exposure to emotional disturbances, and working at a high speed as the association with health is particularly high (10p.p.-20p.p.) and difficult to overcome.